Stenarella domator (Poda) [Hymenoptera: Ichneumonidae], a newly introduced species to the Nearctic, and a summary of adventive Nearctic species of Ichneumonidae - Wahl, David B.; Green, Nathaniel (Zootaxa, 2020)
The western Palaearctic ichneumonid Stenarella domator (Poda) is newly recorded for the Nearctic. Photographs and a new key to the genera of Nearctic Osprynchotina (Cryptinae: Cryptini) are provided. Like other species in the Osprynchotina, S. domator is an ectoparasitoid of aculeate Hymenoptera which use mud/earth in their nests. The 25 species of adventive Nearctic ichneumonids are reviewed, and the implications of their biologies for Nearctic host ranges are discussed.